Metachronous bilateral diabetic mastopathy mimicking breast cancer in a woman with long-standing type 2 diabetes: a case report - Zhixiang Kuang; Wei Ding; Li Li (Frontiers in Medicine, 2026)
Background Diabetic mastopathy is an uncommon benign fibroinflammatory disorder of the breast that often resembles malignancy on clinical examination and imaging. Most reports involve younger women with long-standing type 1 diabetes. Metachronous bilateral disease in an older woman with type 2 diabetes is less often described. Case presentation A 69-year-old woman with a 38-year history of type 2 diabetes treated with self-administered insulin had previously undergone partial excision of a suspicious right-breast mass in 2020. Histology was consistent with sclerosing lymphocytic lobulitis; immunohistochemistry demonstrated both T- and B-cell populations, a CD21-positive follicular dendritic cell network, and a low Ki-67 proliferation index. Four years later, she presented with a palpable left-breast mass. Ultrasonography showed an irregular heterogeneous hypoechoic lesion with indistinct margins and posterior acoustic shadowing, classified as BI-RADS 4b. Mammography showed an irregular mass with a lobulated contour and indistinct margins in a heterogeneously dense breast. On 3.0-T MRI, the mass was irregular and non-circumscribed, with heterogeneous internal enhancement and predominantly progressive enhancement with a slight late decline. High signal was present on diffusion-weighted imaging, but diffusion restriction could not be confirmed because the ADC map and numerical ADC value were unavailable. Core needle biopsy showed marked stromal fibrosis and periductal and perilobular lymphocytic infiltration without malignancy, concordant with diabetic mastopathy. At follow-up on 5 November 2025, the mass remained clinically and sonographically stable. No treatment was administered, and continued surveillance was advised. Conclusion In a patient with long-standing diabetes and previous contralateral diabetic mastopathy, a new suspicious breast lesion may represent metachronous disease. Imaging alone cannot exclude cancer. In selected patients, a benign and imaging-concordant core biopsy may support avoidance of immediate repeat excision, but continued clinical and imaging surveillance remains necessary.